Optimization of a mode of a multiparameter monitoring on an example of a two- parametric monitoring - Цуриков, О. Н.; Терейковский, И. А. (Proceedings of National Aviation University (archive), 1999)
The problems of creation of the system of optimization of a mode of a two-parametric monitoring of aggregates of functional systems of aircrafts are considered. A problem of optimization of a mode of a two-parametric control of optimization is formulated. Substained is the criterion of optimization, the optimization model is constructed